Analisis Perhitungan Weight And Balance pada Loadsheet dalam Menunjang Keselamatan Penerbangan pada Maskapai Air Asia di Bandar Udara Husein Sastranegara Bandung - Egya Shafa Dwi R1; Hodi Hodi (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
The importance of calculating weight and balance on an aircraft to support flight safety is something that must be done by service providers. Mistakes in calculating weight distribution can cause overloads that risk endangering the safety of passengers, crew, and the aircraft itself. This study was conducted at AirAsia Airlines with a focus on the Airbus A320 aircraft at Husein Sastranegara Airport, Bandung. The study used a quantitative method with primary and secondary data collection. Primary data was collected through direct observation in the field, while secondary data was obtained from documents, journals, and related literature. This study analyzed data related to aircraft weight, fuel, passengers, baggage, and cargo to calculate weight and balance on the loadsheet. The results of this study indicate that calculating weight and balance on loadsheets is an important process in ensuring flight safety. Steps involving calculating the weight of passengers, baggage, cargo, fuel, and the distribution of the aircraft's center of gravity ensure that the aircraft operates within the safe limits set by the manufacturer. Based on the analysis of passenger, baggage, cargo, and fuel data, the Zero Fuel Weight (ZFW) was 60,516 kg, Takeoff Weight (TOW) was 67,516 kg, and Landing Weight (LW) was 62,516 kg. All of these parameters are within the specified safe limits. Load management on an Air Asia A320 aircraft when overloading requires special attention to parameters such as Maximum Takeoff Weight (MTOW), Maximum Landing Weight (MLW), and Maximum Landing Weight (MZFW). If an overload occurs, as recorded on the fourth day in Hold 5, the solution that can be taken is to reduce the cargo load on that Hold. For the situation on the fifth day, where the Landing Weight (LW) exceeds the MTOW, the right step is to reduce the amount of fuel.